Perlindungan Relawan di Tengah Krisis Global: Kajian Maqâshid al-Syarî‘ah terhadap Isyarat Al-Qur’an - Nurjanah Nurjanah; Derysmono Derysmono (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article discusses the protection of humanitarian volunteers from the Qur’anic perspective amid the increasing risks faced by humanitarian workers in conflict and disaster areas. The issue is significant because volunteers, medical personnel, journalists, and humanitarian workers often stand at the frontline of saving human lives while being exposed to physical, psychological, legal, and social threats. This study employs a qualitative library research method using thematic Qur’anic interpretation and the maqâshid al-syarî‘ah approach. The data are analyzed by examining Qur’anic verses related to the protection of life, mutual assistance, the prohibition of self-harm, and the respect for human dignity. The study finds that the protection of volunteers is an extension of the principle of ḥifẓ al-nafs, namely the obligation to safeguard human life from harm and destruction. Such protection should not remain merely normative but must be implemented through occupational safety systems, institutional strengthening, legal protection, psychosocial support, and spiritual assistance. This article proposes a Qur’anic-based model of volunteer protection covering physical, mental, spiritual, legal, social, and dignity-based dimensions.